Efektivitas Pelayanan Kesehatan Masyarakat (Studi di Puskesmas Kecamatan Geser Kabupaten Seram Bagian Timur) - Ali Hadi La Dimuru; Andri Rumau (Gorontalo State University, 2021)
Abstract This study will describe the main issues related to the Effectiveness of Public Health Services (Study at the Puskesmas Slide Subdistrict, East Seram Regency). This study uses a qualitative descriptive approach with an effort to present facts on the effectiveness of services. The data sources of this research are primary data and secondary data. Data collection techniques in the form of observation, interviews, data analysis techniques used. The results of the study show effectiveness in public health services at the Puskesmas Slide, East Seram Regency, seen from the facilities and infrastructure that have not been supported. Weak level of knowledge of employees in carrying out the assigned tasks. Employees' skills in completing tasks or jobs are considered low. The level of ability of employees in the process of public health services was found to be still low due to lack of medical facilities, slow processing of referral files resulting in time delays and due to bad weather which affected the level of ability of employees in carrying out their work duties.